Surveillance Mammography After Breast Conservation Therapy: Is Tomosynthesis Worth It?. (August 2019) - Hasan, Shaakir; Gresswell, Steven; Colosimo, Brittany; Weinberger, Kevin; Anderson, Sidney; Abel, Stephen; Bigbee, Matthew; Shindel, Betty; Hilton, Christie; Julian, Thomas; Trombetta, Mark
Abstract : Introduction: We investigated the downstream workup and costs associated with digital breast tomosynthesis (DBT) compared with 2-dimensional full field digital mammogram (FFDM) when employed as initial follow-up imaging in breast conservation therapy. Methods: Between the years 2015 and 2017, 450 consecutive breast conservation therapy patients, ages 32 to 89, with a follow-up DBT (n=162) or FFDM (n=288) were retrospectively reviewed. The primary endpoints were further workup after follow-up mammogram and associated health care costs at 1 year. A single DBT costs an estimated $149 compared with $111 for FFDM, based on Centers for Medicare claims data from the Oncology Care Model. Results: The first posttreatment mammogram was received within 3 (20%), 3 to 6 (32%), or after 6 months (48%) following radiation. Younger patients and those undergoing hypofractionated radiation were more likely to get DBT. There were no differences in stage, receptor status, or mammogram timing between those in the FFDM and DBT groups. The following downstream workup ensued for DBT compared with FFDM imaging: 18% versus 29% short-interval (6-mo) mammogram (odds ratio=1.83, P =0.01), 6% versus 11% breast magnetic resonance imaging (odds ratio=1.90, P =0.08), 4% ultrasound for each, and 3% biopsy for each (1 positive in the FFDM group). Including downstream workup, the estimated cost per patient in the DBT group was $216.14 compared with $237.83 in the FFDM group. Independent predictors for reduced downstream workup per multivariable analysis were the use of DBT and first follow-up mammogram at least 6 months after radiation ( P <0.05). Discussion: Excess workup was reduced with DBT compared with FFDM in the posttreatment setting, which translated to an improvement in cost efficiency in this study.